Progress, impacts and lessons from market shaping in the past decade: a systematic review - Mao, Wenhui; Olson, Katharine; Urli Hodges, Elina; Udayakumar, Krishna (Frontiers in Public Health, 2025)
Market shaping activities have been increasingly used to improve access to health products, such as the advance market commitments used to increase access to the pneumococcal vaccine and COVID-19 vaccines. This paper reviewed the progress and impacts, and identified enablers and barriers of market shaping activities in the past decade. We conducted a systematic review using a structured searching strategy across five academic databases and key actors' websites for gray and white literature published in English since 2012. Two researchers independently performed screening, data extraction, and analysis. Following independent screening, 97 out of 3,006 articles were eligible for analysis. The majority of the articles were qualitative studies and published within the past 5 years. Rapid access to new products, improved availability, and reduced product cost were the most reported impacts. Barriers of market shaping were the disconnection between market shaping interventions and downstream factors, fragmentation and lack of transparency in regulatory processes, and failure to incentivize manufacturers. Enablers included taking end-to-end approaches, coordination across different actors, particularly the national stakeholders and private sector, creating transparent and predictable demand, longer time span, and flexible funding. While market shaping interventions have contributed to the improvement of access to health products, future research should generate additional quantitative evidence, comprehensive impact evaluation, and in-depth studies on the negative impacts of market shaping. Market shaping actors need to adopt definitions and frameworks, apply an ecosystem-wide lens, engage with diverse stakeholders, consider service delivery, and strengthen key capabilities.Systematic review registrationPROSPERO: CRD42023471098, https://www.crd.york.ac.uk/PROSPERO/view/CRD42023471098